2010
DOI: 10.1007/s00421-010-1770-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in postural sway lend insight into effects of balance training, vision, and support surface on postural control in a healthy population

Abstract: Postural sway was assessed [via center of pressure (COP) 95% elliptical area (EA), path length (PL), normalized path length (PL(n)) and sample entropy (SEn)] in four conditions of bipedal upright stance [compliant (Foam) vs. non-compliant (Hard) with eyes-open (EO) vs. eyes-closed (EC)] prior to, and immediately following, a six-week balance training intervention in a group of healthy adults (N = 26). The intervention was comprised of nine exercises progressed in difficulty based on the subjective assessments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 47 publications
7
45
1
1
Order By: Relevance
“…Note that the comparison of values is made possible, although the assessment was done in 2 separate studies, because we processed the signal in the same manner in the 2 studies (down-sampling by 2, no smoothing applied) [26] and used the same parameters to calculate SampEn (r, m) [27]. Our findings are in agreement with previous studies on environmental constraints [7,8]: regularity increases (ie, SampEn decreases) when participants are standing on a compliant surface compared with a stable floor and when visual complexity increases (ie, dark vs light, larger sway of stars compared with minimal sway). In fact, the effect of the support surface on regularity was so dominant that any between-group differences vanished when participants were standing on the stability trainer.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Note that the comparison of values is made possible, although the assessment was done in 2 separate studies, because we processed the signal in the same manner in the 2 studies (down-sampling by 2, no smoothing applied) [26] and used the same parameters to calculate SampEn (r, m) [27]. Our findings are in agreement with previous studies on environmental constraints [7,8]: regularity increases (ie, SampEn decreases) when participants are standing on a compliant surface compared with a stable floor and when visual complexity increases (ie, dark vs light, larger sway of stars compared with minimal sway). In fact, the effect of the support surface on regularity was so dominant that any between-group differences vanished when participants were standing on the stability trainer.…”
Section: Discussionsupporting
confidence: 86%
“…Within static stance tasks, increased DP is equated with poor postural steadiness and reflects lower balance performance [7]. Indeed, in our study, we found moderate to excellent correlations between increased DP on the stars scene and decreased self‐reported balance confidence.…”
Section: Discussionsupporting
confidence: 53%
“…During these conditions, pain intensity was positively correlated with balance impairments, revealing an important role of pain in postural adjustments of obese KOA patients when the environment poses sensory challenges. There are indications that, in healthy subjects, the dynamic sensory reweighting can be optimized via specific training program and enhance balance in altered environments [58]. Therefore, rehabilitation procedures aiming to train sensory reorganization processes, optimizing the time used to solve the sensory conflict and the motor response and decrease pain, may lead to improvements in balance and reduce risk of falls in obese KOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Entropy measures have been successfully used to characterize standing balance [26][27][28], speech signals, and even somewhat predict epileptic seizures and heart attacks [17]. While a direct link between entropy and the sta bility of human walking cannot be proven, given its invariance to initial conditions, connection to Lyapunov exponents and success in diagnosing other biological systems, the construct validity of entropy is quite plausible.…”
Section: Measurementioning
confidence: 98%